1998
DOI: 10.1001/archopht.116.11.1470
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response in the Early Stages of Wound Healing After Excimer Laser Keratectomy

Abstract: To evaluate the inflammatory response and its potential role in the early stages of corneal wound healing after excimer laser keratectomy.Materials and Methods: Lewis rats underwent excimer keratectomy using a 193-nm excimer laser. The central corneas were ablated in 3 depths: group A, epithelium; group B, superficial stroma; or group C, deep stroma. Eyes were harvested 1, 12, 24, and 36 hours, and 1 week after the rats were killed. Immunohistochemistry was used to test frozen sections with monoclonal antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 8 publications
2
64
0
5
Order By: Relevance
“…Laser therapy is used in many biomedical sciences to promote tissue regeneration (Mester, Mester et al 1985;Karu 1999). Many studies involving the low-level laser therapy have shown that the healing process is enhanced by such therapy (Enwemeka 1988;Rochkind, Rousso et al 1989;Nemeth 1993;Grossman, Schneid et al 1998;O'Brien, Li et al 1998;Lilge, Tierney et al 2000;Maegawa, Itoh et al 2000;Schlager, Kronberger et al 2000;Sommer, Pinheiro et al 2001;Wong-Riley, Bai et al 2001; do Nascimento, Pinheiro et al 2004;Eells, Wong-Riley et al 2004;Pinheiro, Meireles et al 2004;Hawkins, Houreld et al 2005). In Table 5 we show the results of LLLT therapy in the pilot study of 38 children with jSpA diagnosed based on both ESSG and ILAR criteria, which we treated, in addition to standard NSAID therapy, with LLLT (Harjacek and Lamot 2008).…”
Section: Treatment Of Jspamentioning
confidence: 99%
“…Laser therapy is used in many biomedical sciences to promote tissue regeneration (Mester, Mester et al 1985;Karu 1999). Many studies involving the low-level laser therapy have shown that the healing process is enhanced by such therapy (Enwemeka 1988;Rochkind, Rousso et al 1989;Nemeth 1993;Grossman, Schneid et al 1998;O'Brien, Li et al 1998;Lilge, Tierney et al 2000;Maegawa, Itoh et al 2000;Schlager, Kronberger et al 2000;Sommer, Pinheiro et al 2001;Wong-Riley, Bai et al 2001; do Nascimento, Pinheiro et al 2004;Eells, Wong-Riley et al 2004;Pinheiro, Meireles et al 2004;Hawkins, Houreld et al 2005). In Table 5 we show the results of LLLT therapy in the pilot study of 38 children with jSpA diagnosed based on both ESSG and ILAR criteria, which we treated, in addition to standard NSAID therapy, with LLLT (Harjacek and Lamot 2008).…”
Section: Treatment Of Jspamentioning
confidence: 99%
“…Although known to kill viruses, bacteria and parasites, and to act as scavenger cells, macrophages also exert deleterious effects on the host by producing excessive free radicals, lytic enzymes and inflammatory cytokines, collectively aggravating tissue damage and being responsible for many of the systemic symptoms associated with acute and chronic inflammation (for reviews see (Duffield, 2003)). In excimer laser ablated corneas, macrophages participate in the inflammatory response contributing to subsequent corneal haze (O'Brien et al, 1998). In the model of cauterisation-induced corneal inflammation, corneal edema, opacity, and vascularization are significantly reduced when macrophages are selectively inhibited (Sonoda et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Under normal circumstances, re-epithelialization progresses rapidly, 4 and the infiltrating leukocytes return to preinjury levels presumably as a result of apoptosis. 5 We recently observed that healing of corneal epithelial wounds is significantly delayed in P-selectin-deficient (P-sel Ϫ/Ϫ ) mice and in wild-type mice after antibodydependent depletion of either circulating neutrophils or platelets.…”
mentioning
confidence: 99%